Effects of exposure to cadmium on calcium metabolism: a population study. Issue 10 (October 1991) - Staessen, J; Amery, A; Bernard, A; Bruaux, P; Buchet, J P; Claeys, F; De Plaen, P; Ducoffre, G; Fagard, R; Lauwerys, R R
Abstract : The objective was to investigate the hypothesis that environmental exposure to cadmium may affect calcium metabolism in the population at large. The 1987 participants (965 men and 1022 women), from 20 to 80 years old, constituted a random sample of the population of four Belgian districts. The urinary excretion of cadmium, a measure of lifetime exposure, averaged 9.3 nmol/24 h in men (range 0.4-324 nmol/24 h) and 7.1 nmol/24 h (range 0.1-71 nmol/24 h) in women. Serum alkaline phosphatase activity and the urinary excretion of calcium correlated significantly and positively with urinary cadmium excretion in both men and women, and serum total calcium concentration negatively with urinary cadmium excretion in men only. The regression coefficients obtained after adjustment for significant covariates indicated that when urinary cadmium excretion increased twofold, serum alkaline phosphatase activity and urinary calcium excretion rose by 3-4% and 0.25 mmol/24 h respectively, whereas in men serum total calcium concentration fell by 6 mumol/l. After adjustment for significant covariates the relation between serum total calcium concentration and urinary cadmium excretion was not significant in women. The findings suggest that even at environmental exposure levels calcium metabolism is gradually affected, as cadmium accumulates in the body. The morbidity associated with this phenomenon in industrialised countries remains presently unknown and requires further investigation.